Trans-catheter mitral valve repair with MitraClip for mitral regurgitation. A case report of an unusual and acute complication of MitraClip migration in the left atrium - Despoina G. Sarridou; Sophia Anastasia Mouratoglou; Christos Chamos; Theofilos Manos; Sokratis Tsagkaropoulos; Georgios Theodoros Karapanagiotidis (Folia Medica)
Transcatheter mitral valve repair with the MitraClip device has become an established therapeutic option for the treatment of symptomatic patients with mitral regurgitation and prohibitive surgical risk. Despite its safe profile when performed in experienced centers, complications such as MitraClip device detachment or migration into the left atrium can occur and pose a significant risk. We report a MitraClip device migration into the left atrium short after its placement in a patient with symptomatic mitral valve regurgitation and a history of previous coronary artery bypass grafting and aortic valve replacement.